The relevance of public complaints commission to Nigeria economic development. (2012)
The paper critically examines the statutory provisions on the Public Complaint Commission (hereinafter called the Commission), and make appropriate suggestions for reform. The Public Complaints Commission is a statutory creation with wide powers of inquiry and investigation: it has wide powers to receive complaints from members of the public against maladministration and misuse of administrative machinery by any public authority and companies or their officials. In Nigeria like other developing countries, the use of administrative power by officers of government and their institutions to oppress, victimize and discriminate against the citizenry is quite common and rampant. The use of administrative powers to flagrantly abuse the citizen's human rights and freedom is also a common occurrence. Thus, there is the need for government to intervene and take definite action to stem this problem that is gradually embarrassing the government, which led to the promulgation of the Public Complaints Commission Decree 311 (now ACT)2 of 1975.